2022
DOI: 10.15537/smj.2022.43.1.20210574
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib as an adjuvant to chemotherapy for patients with metastatic colorectal cancer

Abstract: Objectives: To investigate the anti-tumor activity and tolerability of celecoxib as an adjuvant therapy for patients with metastatic colorectal cancer (CRC). Methods:In this randomized controlled study, 54 patients with metastatic CRC were randomized into 2 groups; the control group (n=28) which received 6 cycles of folinic acid, fluorouracil and irinotecan (FOLFIRI) regimen (5-flourouracil, leucovorin, irinotecan), and the celecoxib group (n=26) which received 6 cycles of FOLFIRI regimen plus celecoxib Origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…VEGFA is an important molecule of VEGF protein family, which could activate downstream signaling pathways by interacting with VEGF Receptor 2 (VEGFR-2), leading to normal angiogenesis or abnormal lesions [18,19] . VEGF could induce ERK molecule and further activate the endothelial cells after primary cerebral hypoxia and glucose deprivation, resulting in cell damage [20] .…”
Section: Resultsmentioning
confidence: 99%
“…VEGFA is an important molecule of VEGF protein family, which could activate downstream signaling pathways by interacting with VEGF Receptor 2 (VEGFR-2), leading to normal angiogenesis or abnormal lesions [18,19] . VEGF could induce ERK molecule and further activate the endothelial cells after primary cerebral hypoxia and glucose deprivation, resulting in cell damage [20] .…”
Section: Resultsmentioning
confidence: 99%
“…[ 186 ] Clinically, due in part to toxicity concerns (GI and cardiac), COX-2 inhibitors have not been aggressively studied for chemoprevention and cancer therapy [ 187 ]. Recently an adjuvant trial of celecoxib for patients with metastatic CRC was reported [ 188 ]. In this small randomized study, 54 patients with metastatic CRC were randomized into 2 groups: a control group that received 6 cycles of the FOLFIRI regimen as compared to a FOLFIRI and celecoxib group (receiving 6 cycles of FOLFIRI plus 200 mg twice daily of celecoxib over 3 months).…”
Section: Attenuation Of Mdsc Functionmentioning
confidence: 99%
“…Fibroblasts make up the majority of mesenchymal cells, and fibroblasts from non-neoplastic colorectal tissue are an important source of COX-2 expression, which is well-established as a crucial process in the development of CRC [8]. Aspirin and other NSAIDs have been investigated in numerous recent trials for chemoprevention of CRC [15][16][17][18][19][20][21][22][23][24]. It is possible that COX-1 activity in activated platelets serves as a signal to induce COX-2 expression by blocking the release of paracrine lipid and protein mediators that induce COX-2 expression.…”
Section: Cox-2 Enzyme In Colorectal Carcinogenesismentioning
confidence: 99%
“…This finding suggests that celecoxib may have anti-angiogenic properties. The ability of celecoxib to inhibit the COX-2 enzyme with subsequent decreased PGE2, which plays a crucial role in the generation of VEGF, may be the cause of the suppression of angiogenesis translated by decreased VEGF levels by the concurrent use of celecoxib with FOLFIRI [ 23 ]. When compared to sporadic forms, COX inhibition has shown statistically significant results in lowering the risk of familial CRC [ 4 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation